The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1177/0363546509335193
|View full text |Cite
|
Sign up to set email alerts
|

Osteotomies about the Knee for Tibiofemoral Malalignment in the Athletic Patient

Abstract: Osteotomies have a role in the active patient with degenerative joint disease of the medial or lateral knee who, for reasons of age or activity level, is not yet a good candidate for prosthetic arthroplasty. Recognition and treatment of malalignment associated with ligamentous instability is essential if long-term good outcomes are to be expected from ligamentous reconstruction. Also, treatment of concomitant malalignment and the unloading of the operative site is now recognized as an important adjunct to any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 61 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…High tibial osteotomies are commonly accepted as an effective treatment for painful arthritis in the varus knee 19 . A recent biomechanical study showed that correction to between 6° and 10° of anatomic valgus completely unloads the medial compartment 32 .…”
Section: Discussionmentioning
confidence: 99%
“…High tibial osteotomies are commonly accepted as an effective treatment for painful arthritis in the varus knee 19 . A recent biomechanical study showed that correction to between 6° and 10° of anatomic valgus completely unloads the medial compartment 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic repetitive stressing of the ACL graft may cause late failure from attenuation. 10 Therefore, revision ACL reconstruction seemed unlikely to have long-term success without correction of the tibial malalignment.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing the tibial slope decreases the posterior vector of force of the distal femur with weight bearing and thus may be favorable after ACL reconstruction. 10 The importance of the tibial slope must be considered when osteotomies are planned prior to ACL reconstruction, and care must be taken to avoid an increase in the tibial slope. The mechanical axis of the lower extremity…”
Section: Discussionmentioning
confidence: 99%
“…The isolated use of HTO as a temporizing measure for symptomatic medial gonarthrosis has diminished over the past few decades. 29 However, several studies have shown that HTO remains a durable procedure for patients returning to intense activity or impact physical activity with unicompartmental disease, 7 particularly in military cohorts where knee arthroplasty may not be prudent. The emerging role of HTO as a chondroprotective measure has also been increasingly recognized, and its surgical indications have expanded to complement a variety of joint-preserving procedures for young patients with subtle malalignment and concomitant knee pathology.…”
mentioning
confidence: 99%
“…27 Despite its growing acceptance among younger patients, there are limited reports on clinical outcomes after HTO in this patient subset, 11,14,20 particularly in more highdemand cohorts. 7,23,28,30 The existent literature varies widely by patient demographics, surgical indications, length of follow-up, surgical technique, and presence of associated procedures, and many studies primarily focus on conversion to knee arthroplasty as an isolated endpoint in assessing the success after HTO. 4,12 Few studies to date have evaluated patient-reported and functional outcomes in athletic populations after HTO, 9,23 and no study has reported on the ability of HTO to return patients to occupations requiring strenuous physical performance.…”
mentioning
confidence: 99%